2021
DOI: 10.1017/s0022149x21000237
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Strongyloides stercoralis among patients with leptospirosis in northern Iran: a descriptive cross-sectional study

Abstract: Strongyloidiasis and leptospirosis are neglected tropical diseases that have affected many countries across the world. In this study, we evaluated the seroprevalence of Strongyloides stercoralis among patients with leptospirosis in northern Iran. We evaluated 156 laboratory- or clinically confirmed leptospirosis cases. The overall seroprevalence of S. stercoralis was 32.0% (95% confidence interval (CI): 27.4–36.5%, 50/156). Seropositivity was significantly associated with agricultural activities (odds ratio (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Co-infections and occupational information are also relevant pieces of the puzzle, as studies have shown a higher exposure to S. stercoralis larvae among patients with leptospirosis and those working in agriculture, respectively (Varzegar et al , 2021). Some recent studies highlight the need to implement stringent screening due to high seroprevalence rates in migrant populations coming to Europe, highlighting serology as an optimal approach (Requena-Méndez et al , 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Co-infections and occupational information are also relevant pieces of the puzzle, as studies have shown a higher exposure to S. stercoralis larvae among patients with leptospirosis and those working in agriculture, respectively (Varzegar et al , 2021). Some recent studies highlight the need to implement stringent screening due to high seroprevalence rates in migrant populations coming to Europe, highlighting serology as an optimal approach (Requena-Méndez et al , 2020).…”
Section: Resultsmentioning
confidence: 99%